ALK3 undergoes ligand-independent homodimerization and BMP-induced heterodimerization with ALK2 - Träger, Lisa; Muckenthaler, Martina (Free radical biology and medicine, 2018)
The bone morphogenetic protein (BMP) type I receptors ALK2 and ALK3 are essential for expression of hepcidin, a key iron regulatory hormone. In mice, hepatocyte-specific Alk2 deficiency leads to moderate iron overload with periportal liver iron accumulation, while hepatocyte-specific Alk3 deficiency leads to severe iron overload with centrilobular liver iron accumulation and a more marked reduction of basal hepcidin levels. The objective of this study was to investigate whether the two receptors have additive roles in hepcidin regulation. Iron overload in mice with hepatocyte-specific Alk2 and Alk3 (Alk2/3) deficiency was characterized and compared to hepatocyte-specific Alk3 deficient mice. Co-immunoprecipitation studies were performed to detect the formation of ALK2 and ALK3 homodimer and heterodimer complexes in vitro in the presence and absence of ligands. The iron overload phenotype of hepatocyte-specific Alk2/3-deficient mice was more severe than that of hepatocyte-specific Alk3-deficient mice. In vitro co-immunoprecipitation studies in Huh7 cells showed that ALK3 can homodimerize in absence of BMP2 or BMP6. In contrast, ALK2 did not homodimerize in either the presence or absence of BMP ligands. However, ALK2 did form heterodimers with ALK3 in the presence of BMP2 or BMP6. ALK3-ALK3 and ALK2-ALK3 receptor complexes induced hepcidin expression in Huh7 cells. Our data indicate that: (I) ALK2 and ALK3 have additive functions in vivo, as Alk2/3 deficiency leads to a greater degree of iron overload than Alk3 deficiency; (II) ALK3, but not ALK2, undergoes ligand-independent homodimerization; (III) the formation of ALK2-ALK3 heterodimers is ligand-dependent and (IV) both receptor complexes functionally induce hepcidin expression in vitro.
Gesehen am 03.05.2019